Assemblr Edu AR-GeoGebra: Development of three-dimensional shapes material in junior high school on students' - Junariah Junariah; Anton Nasrullah; Isnaini Mahuda; Ratu Khoirotun Nisa; Silvia Ratnasari; Mohamad Basri Nadzeri (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to develop and evaluate Augmented Reality (AR) integrated with GeoGebra learning media to enhance students’ conceptual understanding and learning interest in three-dimensional shapes at the junior high school level. This research employed a Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, and Disseminate). The study involved 29 ninth-grade students at a state junior high school in Cilegon, Banten, Indonesia. Data were collected through validation questionnaires, student response surveys, and conceptual understanding tests (pretest–posttest). The results showed that the developed learning media achieved high validity, with scores of 85% for media validation and 82% for material validation. The practicality level was also high, with a student response score of 89.2%, indicating that the media was easy to use and engaging. In terms of effectiveness, students’ conceptual understanding improved, as indicated by an increase in the average score from 60 (pretest) to 80 (posttest), with a gain score of 0.67 (moderate category). Additionally, students’ learning interest increased from the “fair” category to the “good” category. These findings indicate that AR-GeoGebra-based learning media has the potential to improve students’ conceptual understanding and learning interest in three-dimensional shapes. However, the results should be interpreted cautiously due to the limited sample size and the absence of inferential statistical testing. Therefore, further studies with larger samples and more rigorous analysis are recommended.